Microfinance and Moneylenders: Long-Run Effects of MFIs on Informal Credit Market in Bangladesh - Berg, Claudia; Emran, M. Shahe; Shilpi, Forhad (World Bank, Washington, D.C., 2013)
Using two surveys from Bangladesh, this paper provides evidence on the effects of microfinance competition on village moneylender interest rates and households' dependence on informal credit. The views among practitioners diverge sharply: proponents claim that competition of microfinance institutions reduces both the moneylender interest rate and households' reliance on informal credit, while the critics argue the opposite. Taking advantage of recent econometric approaches that address selection on unobservables without imposing standard exclusion restrictions, this paper finds that microfinance competition does not reduce moneylender interest rates, thus partially repudiating the proponents. The effects are heterogeneous; there is no perceptible effect at low levels of coverage, but when microfinance coverage is high enough, the moneylender interest rate increases significantly. In contrast, households' dependence on informal credit tends to go down after they become a member of a microfinance institution, which contradicts part of the critic's argument. The evidence is consistent with a model where microfinance institutions draw away better borrowers from the moneylender, and fixed costs are important in informal lending.